Synthesis and crystal structure of 6,6′-((1E,11E)-5,8-dioxa-2,11-diazadodeca-1,11-diene-1,12-diyl) bis(2,4-di-tert-butylphenol), C36H56N2O4 - Zhang Ya-Fang; Zhao Ji-Xing (Zeitschrift für Kristallographie - New Crystal Structures)
C36H56N2O4, monoclinic, P21/c (no. 14), a = 18.1240(10) Å, b = 17.1409(9) Å, c = 11.3102(6) Å, β = 95.659(2)°, V = 3,496.5(3) Å3, Z = 4, Rgt(F) = 0.0638, wRref(F2) = 0.1634, T = 173 K.